IN-SITU ASSESSMENT OF PHENOTYPIC DIVERSITY IN CAJANUS SCARABAEOIDES (L.)THOUARS - NILAMANI DIKSHIT; VISHNU K GITE; NATARAJAN SIVARAJ (The Bioscan, 2015)
In-situ assessment of phenotypic diversity in 13 wild populations of Cajanus scarabaeoides (L.) Thouars were carried out in five districts of Vidharbha region of Maharashtra state, India. Significant variability in qualitative traits ranging from stem pigmentation (light green, green to purple and some accessions turned even red during maturity), flower pattern (sparse to medium streaks on yellow flower) and seed coat colour (brown, mottled to black) were observed. Plant height ranged from 80.0-190.0 cm, number of branches per plant (3.0-10.0), pod length (1.7-3.0 cm), pod width (0.7-1.0 cm), number of seeds per pod (4.0-6.0), number of pods per plant (5.7- 30.0) and 100 seed weight (1.47-3.02g). Promising lines were identified for select traits which can be utilized in pigeonpea crop improvement programme. For example, D/G-9, a collection from Gujgawan, Chandrapur district was recorded promising for plant height (190.0 cm), number of seeds per pod (6.0) and number of pods per plant (30.0). DIVA-GIS grid maps were generated to delineate the diversity rich pockets for select quantitative traits. GIS analysis indicated that Northern Vidarbha region was the rich pocket of C. scarabaeoides diversity.